Vertical Impedance of Rigid Shallow Foundation on Layered Water-Saturated Soil - Trofymchuk, Oleksandr; Savytskyi, Oleh (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2019)
Methods have been developed for numerical analysis the vertical oscillations of rigid plate with a liquidimpermeable sole rested on the layer (Biot’s model) with a rigidly restrained lower edge. The plate sole is liquid-impermeable. The analysis of the impedance functions depending on the oscillation frequency, the geometry of the system and the mechanical parameters of the soil model is carried out.